2021
DOI: 10.1186/s12014-020-09309-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the potential of Pap test fluid and cervical swabs to serve as clinical diagnostic biospecimens for the detection of ovarian cancer by mass spectrometry-based proteomics

Abstract: Background The purpose of this study was to determine whether the residual fixative from a liquid-based Pap test or a swab of the cervix contained proteins that were also found in the primary tumor of a woman with high grade serous ovarian cancer. This study is the first step in determining the feasibility of using the liquid-based Pap test or a cervical swab for the detection of ovarian cancer protein biomarkers. Methods Proteins were concentrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…The low sensitivity of CA125 has led to the development of additional serum proteins as candidates for biomarkers that could aid the accuracy of CA125 as an adjunct marker. The combination of CA125 with other biomarkers is an approach that has been pursued in an effort to overcome the limitation of the single use of CA125 [ 79 , 80 , 81 ].…”
Section: Proteomics In Ovarian Cancermentioning
confidence: 99%
“…The low sensitivity of CA125 has led to the development of additional serum proteins as candidates for biomarkers that could aid the accuracy of CA125 as an adjunct marker. The combination of CA125 with other biomarkers is an approach that has been pursued in an effort to overcome the limitation of the single use of CA125 [ 79 , 80 , 81 ].…”
Section: Proteomics In Ovarian Cancermentioning
confidence: 99%
“…In 2021, Boylan et al [28] reported a proteomic study in samples from patients with advanced CC. The samples were collected by Pap smear, cervical swab, or from ovarian tumor tissue.…”
Section: Cervical-vaginal Fluidmentioning
confidence: 99%
“…It is used in the analysis and search of cancer biomarkers and relies on reproducible techniques of sample selection, purification, and storage [45,51]. The main techniques used for the large-scale analysis of comparative data are 2-DE and MS [28,51]. MS acquires the spectral data of peptides (from digested proteins), and bioinformatics tools are then necessary to identify the peptides and corresponding consensus proteins, such as MASCOT, Protein Pilot, Skyline, and DAVID Bioinformatics Resources, among Globally, proteomics can characterize the function and location of proteins and is broadly divided into three categories: (1) Functional Proteomics, which refers to various proteomic approaches that allow the study and characterization of protein signaling, the mechanisms of protein-related disease, and protein-drug interactions [46].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While Type I tumors have a high frequency of KRAS and BRAF mutation, Type II tumors have a high frequency of TP53 mutations [31][32][33][34]. Other biospecimens such as effusions, pap smear fluids, and cervical swabs, are also valuable for understanding OC pathobiology and represent sources of markers that can predict clinical outcomes [35,36]. For example, a 9-biomarker panel in ovarian cyst fluids has been shown to discriminate between type 1 and type 2 tumors [37].…”
Section: Protein Biomarkers Associated With Ocmentioning
confidence: 99%